PENGEMBANGAN MEDIA GAME EDUKASI BERBASIS ANDROID MATERI BILANGAN BULAT SEKOLAH MENENGAH PERTAMA - Rohmah, Rosyidatur; Kurniawan, Choirul; Abidin, Munirul (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
This study aims to address the low learning motivation and difficulties faced by junior high school students regarding the topic of integers. This is a Research & Development study that aims to: (1) produce an immersive educational game medium based on the quiz.zep.us platform; (2) determine the media's validity (feasibility) level; and (3) determine the media's practicality level. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 16 seventh-grade students at MTS Miftahul Ulum Pujon. Data collection instruments included expert validation questionnaires and student response questionnaires. The data were analyzed using quantitative descriptive statistics. The results showed that: (1) The quiz.zep.us-based educational game product was successfully developed. (2) The media validity level obtained an average score of 88.75%, categorized as "Highly Feasible." (3) The media practicality level obtained a score of 93% from student responses, categorized as "Highly Practical." It is concluded that this educational game medium is highly feasible and highly practical for use as an innovative, alternative learning medium for the topic of integers.